P264 Investigation of inconsistent score patients by using Lewis Score and CECDAI in Crohn's disease. (16th January 2018) - Omori, T; Hosoya, S; Yasuhiro, K; Kambayashi, H; Murasugi, S; Ito, A; Yonezawa, M; Nakamura, S; Tokushige, K
Abstract: Background: Small bowel capsule endoscopy (SBCE) for Crohn's disease (CD) with small bowel lesions is a low-invasive method that enables visualisation of the small bowel mucosa. Two scoring methods are used to evaluate the images obtained: the Lewis score (LS) and the capsule endoscopy Crohn's disease activity index (CECDAI). However, the scores of some subjects are not consistent between these scoring methods. The aim was to evaluate the characteristics of subjects who displayed inconsistency between scoring methods by using small bowel capsule endoscopy (SBCE) data of CD patients with small bowel lesions. Methods: The subjects included 93 CD patients with small bowel lesions who underwent SBCE between June 2010 and May 2017. SBCE was carried out a total of 162 times in these patients, including 104 times in men, 49 times for small bowel CD, and 113 times for small-and-large bowel CD. LS and CECDAI score were calculated, and subjects who showed inconsistency between the scoring methods were identified. The characteristics of the scores in the inconsistent subjects and their relationships with the clinical disease activity index (CDAI) and biomarkers were analysed. Results: The 111 subjects with LS below 135 were divided into a consistent-CECDAI group ( n = 69) and an inconsistent-CECDAI group ( n = 42). In the inconsistent-CECDAI group, 8 subjects (19%) had a CECDAI score of 3.8 to 5.8 and 34 subjects (81%) had a CECDAI score of 5.8 or higher. The difference between the consistent- and inconsistent-CECDAI groups was that LS was higher in the latter (5.4 ± 9.3 and 42 ± 38, respectively; p < 0.0001). In addition, the inconsistent-CECDAI group had a significantly higher rate of inflammatory signs at multiple sites than the consistent-CECDAI group ( p < 0.0001). the CDAI score was significantly higher in the inconsistent-CECDAI group than in the consistent-CECDAI group, at 116 ± 78 vs. 83 ± 63 ( p = 0.01). Additionally, C-reactive protein (CRP) was also significantly higher, at 0.76 ± 0.96 vs. 0.52 ± 2.32 ( p = 0.0007). Among the 75 subjects with a CECDAI score below 3.8, the mean LS of the 6 LS-inconsistent subjects was 238 ± 46. With all 6 subjects, the LS inflammation score was 0, and the relatively high LS score was, therefore, due to stenosis. No significant differences in the CDAI or CRP were found between the LS-consistent group ( n = 69) and LS-consistent group ( n = 6). Conclusions: Even among subjects with a LS below 135, some had a CECDAI score of 3.8 or higher, and disease activity was shown on the basis of clinical symptoms and biomarkers. In addition, even among subjects with a CECDAI score below 3.8, there were some subjects with a high LS due to stenotic lesions. These findings suggest that CECDAI score is more accurate for assessing the clinical state than LS.